Kontribusi Asupan Zat Gizi terhadap Kejadian Anemia Pada Remaja Putri di SMAN 7 Kendari - Harleli Harleli (Yayasan Literasi Sains Indonesia, 2026)
Anemia is one of the public health problems frequently found in developing countries, particularly among adolescent girls. This condition is generally influenced by the monthly menstrual cycle, which increases iron loss and consequently reduces hemoglobin levels below the normal threshold. This study aimed to analyze nutrient intake in relation to the incidence of anemia among adolescent girls. The research employed a quantitative design with an analytic cross-sectional approach. The sample consisted of 64 female students at SMAN 7 Kendari. Samples were selected using stratified random sampling from the population that met the inclusion and exclusion criteria. The inclusion criterion was female students of SMAN 7 Kendari who were in good health at the time of data collection, while the exclusion criteria were students who were menstruating during data collection, those with menstrual cycle disorders, and those with no history of malaria or worm infections based on a physician’s diagnosis. Data were collected through observation and interviews using a respondent characteristics questionnaire, along with dietary intake assessment using the SQ-FFQ method. Data analysis was performed using bivariate tests with the Chi-Square test at a significance level of α = 0.05. The bivariate analysis showed a significant relationship between protein intake (ρ = 0.026), iron intake (ρ = 0.000), and vitamin C intake (ρ = 0.001) with the incidence of anemia among adolescent girls at SMAN 7 Kendari.